Adaptation Of The Variable Neighborhood Search Heuristic To Solve The Vehicle Routing Problem - Imran, Arif; Okdinawati, Liane (Jurnal Teknik Industri, 2011)
The vehicle routing problem is investigated by using some adaptations of the variable neighborhood search (VNS). The initial solution was obtained by Dijkstra’s algorithm based on cost network constructed by the sweep algorithm and the 2-opt. Our VNS algorithm use several neighborhoods which were adapted for this problem. In addition, a number of local search methods together with a diversification procedure were used. The algorithm was then tested on the data sets from the literature and it produced competitive results if compared to the solutions published.